The Implementation of Qawāʿid Fiqhiyyah in Islamic Securities Crowdfunding - Alfan Jawahir Muhammad; Zainal Arif; fina Nurafni (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
Islamic Securities Crowdfunding (ISC) is an innovation in Islamic finance that offers an alternative funding mechanism in accordance with Sharia principles. As financial technology continues to develop, ISC enables the public to participate in investment activities in a more inclusive and transparent manner. However, its implementation must consistently adhere to the principles of qawāʿid fiqhiyyah (Islamic legal maxims) to avoid elements of riba (usury), gharar (uncertainty), and maysir (gambling). This study examines the application of qawāʿid fiqhiyyah in Islamic Securities Crowdfunding by referring to DSN-MUI Fatwa No. 140/DSN-MUI/VIII/2021. It analyzes several Islamic legal maxims, including the permissibility of commercial transactions unless explicitly prohibited, the principle of preventing harm, and the relationship between legal rulings and their effective causes (ʿillah). Using a literature review method and a descriptive-analytical approach, this research explores how ISC can be implemented in accordance with Indonesia's Islamic financial regulations. The findings indicate that ISC has significant potential to enhance Islamic financial inclusion while upholding the principles of transparency, justice, and public welfare (maṣlaḥah). The application of qawāʿid fiqhiyyah in ISC ensures that every transaction complies with Islamic law, making it a sustainable investment solution that aligns with the objectives of Islamic law (maqāṣid al-sharīʿah).